Evangelical Christianity and democracy in Africa - Ranger, T. O. (Terence O.) (Oxford ; New York : Oxford University Press, 2008)
One of four projected volumes to emerge from a massive, Pew-funded study that sought to answer the question: What happens when a revivalist religion based on scriptural orthodoxy participates in the volatile politics of the Third World? This book considers the case of Africa.
Introduction : Evangelical Christianity and democracy in Africa / Terence O. Ranger -- Evangelicals, Muslims, and democracy : with particular reference to the Declaration of Sharia in northern Nigeria / Cyril Imo -- Evangelical attitudes toward democracy in Kenya / John Karanja -- President Frederick Chiluba and Zambia : Evangelicals and democracy in a "Christian nation" / Isabel Apawo Phiri -- Foundations for democracy in Zimbabwean Evangelical Christianity / Isabel Mukonyora -- Evangelicals and democracy in Mozambique / Teresa Cruz e Silva -- From apartheid to the new dispensation : Evangelicals and the democratization of South Africa / Anthony Balcomb -- Evangelical Christianity and democracy in Africa : a response / Paul Gifford.
Includes bibliographical references (p. [243]-259) and index.
Description based on print version record.
Keywords: Evangelicalism -- Political aspects -- Africa, Sub-Saharan.; Democracy -- Religious aspects -- Christianity; Christianity and politics -- Africa, Sub-Saharan.; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Electronic books